Makunaima: a hero serving the social order (Revista de Crítica Literaria Latinoamericana, 2012)
This work presents Makunaima as the main character of the best-known and extensive oral legendary tradition of the inhabitants from the extreme north of South America, the triple border between Brazil, Venezuela and Guyana –etnographically designated as the circum-Roraima region, in order to examine the cultural role this character had before becoming the “heroe of our people” through the work of Mário de Andrade.
Keywords: legendary; Makunaima; heroe; culture